Characterisation and proteomic profiling of continuously exposed Cu-resistant variants of the Caco-2 cell line. (June 2020) - O'Doherty, Charles; Keenan, Joanne; Henry, Michael; Meleady, Paula; Sinkunaite, Indre; Clynes, Martin; O'Sullivan, Finbarr; Horgan, Karina; Murphy, Richard
Abstract: Studies in hepatic systems identify multiple factors involved in the generation of copper resistance. As the intestine is the route of exposure to dietary copper, we wanted to understand how intestinal cells overcome the toxic effects of high copper and what mechanisms of resistance develop. Using the intestinal cell line Caco-2, resistance was developed by serial subculture in 50 μM copper in inorganic (CuSO4 ) or organic (Cu proteinate) forms. Caco-2 variants exhibited resistance to copper and retained the non-monotonic dose response while displaying stable phenotypes following repeated subculture in the absence of copper. Phenotypic changes on exposure to copper in parental Caco-2 cells included significantly increased total protein yield, ROS, SOD, metallothionein expression, GSH and total glutathione. These phenotypic changes were not replicated in resistant variants on a per cell basis. Quantitative label-free LC-MS/MS proteomic analysis identified 1113 differentially expressed proteins (DEPs) between parental Caco-2 and resistant cells. With some exceptions, most of the DEPs were overexpressed to a low level around 2-fold suggesting resistance was supported by multiple small changes in protein expression. These variants may be a useful tool in studying the toxicity of stress responses in further Cu-related studies. Graphical abstract: Unlabelled Image Highlights: Continuous exposure of Caco-2 cells to copper resulted in Cu-resistance generation. Copper toxicity, growth and phenotypic profiles were altered in Cu-resistant Caco-2. ROS, SOD and GSSG increased in Cu-exposed parent but not Cu-resistant Caco-2 cells. Quantitative proteomic profiling identified 1113 differentially expressed proteins.